Find an equation of the inverse of the function f(x) = \frac{x - 6}{ 3 - x}. Find the Inverse Function f(x)= \frac{1}{(x+7)} Find the inverse function of f(x)= x - \frac{2}{5} algebraically. Find the inverse of the function f(x) = \ln(7 - 3x). ...
We get that the function is undefined atx=−2, so the domain of the function is all real numbers except for -2. That is: Domain of f(x)={xis a real number|x≠−2} Step 3:To find the equation of the inverse, we first replacef(x)with y. ...
The function declaration ( f(x)) varies according to ( x), but the input function( m) only contains the variable( m). Assume ( f(m)=m). ( f(m)=m) Replace ( f(m)) with ( y). ( y=m) Interchange the variables. ( m=y) Rewrite the equation as ( y=m). ( y=m) ...
百度试题 结果1 题目find the inverse of the function:f(x)= (4x-1)/(2x+3) 相关知识点: 试题来源: 解析 反函数=(3x-1)/(4-2x) 反馈 收藏
Inverse of a Function: To find the inverse of a function, follow the steps given below. 1. First replace {eq}f(x) {/eq} by {eq}y {/eq}. 2. Replace all {eq}x {/eq} by {eq}y {/eq} and {eq}y {/eq} by {eq}x {/eq}. 3. Solve for {eq}y {/eq}. 4. ...
Find the inverse equation of f(x)=(x−6)2−1. Inverse Function:In mathematics, the inverse function is the opposite of the given function. In trigonometry, it is used to evaluate some specific angles when angles are not in standard form. The inverse function is easily convertible from ...
Find the inverse of the function:f:Z→Zdefined byf(x)=[x+1],where [.] denotes the greatest integer function. View Solution Letf:D→R, where D is the domain off. Find the inverse offif it exists: Letf:[0,3]→[1,13]is defined byf(x)=x2+x+1, then findf−1(x). ...
试题来源: 解析 【解析】 \$f ^ { - 1 } ( x ) = ( x - 1 ) ^ { \frac { 1 } { 3 } }\$ 结果一 题目 Find the inverse of the functionf(x)=z3+1 答案 =^1(ω)=(n-1)^(1/2) 相关推荐 1Find the inverse of the functionf(x)=z3+1 反馈 收藏 ...
百度试题 结果1 题目Find the inverse of the function, y=2x+10 ( ) A. 15x+2=f^(-1)(x) B. 12x-5=f^(-1)(x) C. -2x-10=f^(-1)(x) D. x⋅ 5=f^(-1)(x) 相关知识点: 试题来源: 解析 B 反馈 收藏
Inverse Function: The inverse function of a function {eq}f(x) {/eq} is equal to {eq}g(x) {/eq} if the following equations hold: {eq}f(g(x)) = x {/eq} {eq}g(f(x)) = x {/eq} To determine the inverse {eq}g(x) {/eq} given {eq}f(x) ...